Progestins Inhibit Tumor Necrosis Factor α–Induced Matrix Metalloproteinase 9 Activity via the Glucocorticoid Receptor in Primary Amnion Epithelial Cells. (September 2019) - Allen, Terrence K.; Nazzal, Matthew N.; Feng, Liping; Buhimschi, Irina A.; Murtha, Amy P.
Progestins have been recommended for preterm birth prevention in high-risk women; however, their mechanism of action still remains an area of debate. Medroxyprogesterone acetate (MPA) has previously been shown to significantly inhibit tumor necrosis factor α (TNFα)-induced matrix metalloproteinase 9 (MMP9) messenger RNA (mRNA) expression and activity in primary amnion epithelial cells, a process that may lead to preterm premature rupture of membranes. A mechanism that explains MPA's inhibition of TNFα-induced MMP9 mRNA expression and activity in primary amnion epithelial cells is unclear since these cells lack the classic nuclear progesterone receptor but express a membrane-associated progesterone receptor—progesterone receptor membrane component 1 (PGRMC1) along with the glucocorticoid receptor (GR). Primary amnion epithelial cells harvested from healthy term pregnant women at cesarean section were treated with PGRMC1 (to knockdown PGRMC1 expression), GR (to knockdown GR expression), or control small interfering RNA (siRNA; 10 nm) for 72 hours, pretreated with ethanol or MPA (10 −6 M) for 6 hours, and then stimulated with or without TNFα 10 ng/mL for 24 hours. Real-time quantitative polymerase chain reaction and gelatin zymography were used to quantify MMP9 mRNA expression and activity, respectively. Experimental groups were compared using 1-way analysis of variance. Both TNFα-induced MMP9 mRNA expression and activity were significantly inhibited by pretreatment with MPA; however, only the inhibition of TNFα-induced MMP9 activity was partially reversed with PGRMC1 siRNA. However, GR siRNA reversed both the inhibition of TNFα-induced MMP9 mRNA expression and activity by MPA. This study demonstrates that MPA mediates its anti-inflammatory effects primarily through GR and partially through PGRMC1 in primary amnion epithelial cells.